Efektifitas Terapi Musik Terhadap Penurunan Rasa Nyeri Pada Ibu Post Sectio Caesarea - Pristiani, Anik; Jamhariyah, Jamhariyah; Prasetyo, Hendro (Malang Journal of Midwifery (MAJORY), 2021)
Sectio caesarea is the removal of the fetus through the abdominal wall incision (laparotomy) and uterine wall (hysterectomy). During the postoperative period, the nursing process is directed to stabilize the patient's physiological balance and relieve pain. Physiological reactions to pain include autonomic nerve responses such as breathing speed, increased pulse and increased heart rate. Musik therapy as a nonpharmacological therapy can relieve pain because when given musik, the midbrain releases beta endorphin hormone which can eliminate pain neurotransmitters. This study aims to examine the literature, articles and documents of research findings that identify the effectiveness of musik therapy for pain reduction in post sectio cesarean mothers. This study used a qualitative descriptive approach and type of literature study research. Data collection by literature review was obtained through Google Scholar by typing keywords, sources published in 2011 to 2018. 13900 research articles were obtained, identification, screening, eligibility. 10 relevant research articles were obtained. Journal review results found that from 10 journals that have been analyzed show the influence of musik therapy on pain management in Sectio Caesarea postoperative patients with strong asymp sig correlation. In accordance with the journal analysis, respondents' pain reduction was assessed based on the NRS pain scale so as to produce homogeneous data. It is recommended that musik therapy as an independent intervention in nursing and maternity obstetrics can be implemented to reduce pain in post-sectional Caesarean patients.